2007
DOI: 10.1002/gps.1793
|View full text |Cite
|
Sign up to set email alerts
|

Profile of psychiatric disorders and life events in medically ill elderly: experiences from geriatric clinic in Northern India

Abstract: Mental disorders are common among medically ill elderly patients, but they are poorly recognized and treated. Assessment of the psychiatric morbidity will help in strengthening psycho-geriatric services and thus, improve the quality of life of the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 17 publications
4
18
0
1
Order By: Relevance
“…The prevalence and pattern of co-morbidities among elderly depressed patients who attended primary care in our study were similar to those which were seen various other studies [6][7][8], with hypertension and diabetes being the most common co-morbidities. The presence of co-morbidities may lead to disabilities which further the depression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence and pattern of co-morbidities among elderly depressed patients who attended primary care in our study were similar to those which were seen various other studies [6][7][8], with hypertension and diabetes being the most common co-morbidities. The presence of co-morbidities may lead to disabilities which further the depression.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, elderly patients were more likely to suffer from depression as compared to the middle aged. This difference was statistically significant; this was similar to findings of other studies which were done among geriatric patients in psychiatry healthcare and old age homes [6][7][8]. However, some studies [9] found that a majority of the patients with psychiatric morbidity were in the age group of 16-45 years and that most were suffering from severe mental illness; of which bipolar affective disorder (45%) and schizophrenia (35.9%) were the two most common ones.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistent with previous studies. 13,29,31,32 Recent stressful life events should be identified and suitable support, self-help groups, and counseling need to be in place in the community.…”
Section: Discussionmentioning
confidence: 99%
“…The clinic-based studies have reported neurotic disorders in 5-19.8 % of elderly, a significant proportion of which are likely to be anxiety disorders (Prasad et al 1996;Singh et al 2004;Prakash et al 2007). Not much original research from India is available on other aspects of anxiety disorders in the elderly.…”
Section: Anxiety Disordersmentioning
confidence: 97%
“…Several epidemiological studies have been conducted in community (Table 1) (Ramachandran et al 1979;Seby et al 2011) as well as in hospital settings (Prasad et al 1996;Prakash et al 2007). The prevalence of psychiatric morbidity among elderly (≥60 years) residing in community has ranged between 8.5 and 42.2 %.…”
Section: Epidemiological Studiesmentioning
confidence: 98%